A Linguistic Analysis of Identity, Emotion, And Gender in Best of Five Songs by Maroon 5 - Waldan, Bavari Muhammad; Juanda; Sari, Retno Purwani (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2025)
This study examines the language formulation of identity, emotion, and gender in five commercially and culturally significant songs by the American pop-rock band Maroon 5: